SOSIALISASI PENDAFTARAN ONLINE PELAYANAN KESEHATAN DI KABUPATEN TUBAN - eva silviana rahmawati; Muhammad Sudrajad; Didik Suharsoyo; Surotul Ilmiah; sugiyono; Siska Fajarwati Awwaliyah (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2023)
This research is motivated by the author's involvement in the online health service registration program in Tuban Regency. The thing that influenced the occurrent of this research was due to the lack of public knowledge about online registration services due to the low level of public knowledge. The purpose of this study is to provide socialization of understanding about health services and alson the steps for registering health services and also to the steps for registering health services online and the benefits of online registration. This research is supported by theoretical conceptual ideas about: the concept of attitude, the concept of population, and the concept of counseling. This socialization had a significant effect on the people in Tuban Regency. Suggestions that can be given by researchers: It is hoped that the community will already know more about the online registration service form after the completion of this socialization. For future researchers who are interested in conducting research with the same research, it is hoped that they will further develop research from apects that have not been discussed in this study.